Biologic restoration of a traumatized maxillary central incisor in a toddler: A case report - Sheen Ann John; S Anandaraj; Sageena George (Wolters Kluwer Medknow Publications, 2014)
Trauma to the anterior teeth is relatively common in young children and teenagers. Traumatized anterior teeth require quick functional and aesthetic repair, and poses a challenge to the dental practitioner owing to the lack of co-operation ceded and the longer time invested. Reattachment of tooth fragment should be the first choice to restoring teeth when a usable fragment is available, since it gives a psychological and aesthetic advantage over the conventional technique. With the vast improvement in adhesive technology, reattachment is definitely a predictable treatment option for very young children. This paper describes the treatment of a 2½ year old female child who sustained crown-root fracture, extending subgingivally, in primary upper central incisor.